Cardiovascular and autonomic response induced by a 20-week military training programme in young healthy South African males - Zondi, P C (South African Journal of Sports Medicine, 2015)
Background. Studies investigating the relationship between exercise and haemodynamic regulation conducted in older caucasian and black African populations suggest that lifestyle modification is effective in the management of numerous disease processes. There are few longterm studies in young healthy populations and even less is known about the influence of habitual exercise on autonomic and haemodynamic variables in young black African subjects. Objective. To investigate the benefit of prolonged exercise on cardiovascular and haemodynamic variables in young healthy black African males. Methods. Fifty-five healthy male volunteers between 18 and 22 years of age participated in this prospective 20-week medium- to highintensity exercise intervention study with a self-control design. The Finometer Pro (Finapres Medical Systems, the Netherlands) was used for non-invasive data sampling of a number of cardiovascular and autonomic variables. Results were generated by computer algorithm and were analysed using non-parametric Wilcoxon signed rank tests. Results. Significant (p<0.05) cardiovascular changes included an increase in aerobic capacity, stroke volume, cardiac output and ejection fraction, and a decrease in diastolic blood pressure and heart rate. There was a significant decrease in total peripheral resistance and ascending aorta impedance. Systolic blood pressure, mean arterial pressure and arterial compliance remained unchanged, while the decrease in blood pressure variability was not statistically significant (p>0.05). Conclusion. The measured changes suggest a favourable response to exercise and imply that habitual exercise may be an important lifestyle modification for reducing the risk of cardiovascular disease in young black African males.